The Consumer Perceptions of Digital Marketing for Agricultural Products in Kendari City - Dimas Muhammad Taufiq; Surni Surni; Weka Gusmiarty Abdullah (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2024)
Digital marketing has grown rapidly as an integral part of marketing strategies in the digitalization era, and the agricultural sector is no exception. However, studies on consumer perceptions of agricultural products towards the application of digital marketing, especially in the Kendari area, are still limited. This study aimed to determine consumers' perceptions of agricultural products towards digital marketing in Kendari City. The research was conducted from January to March 2024, involving 70 respondents who are consumers of agricultural products in Kendari City. The research variables included Search Engine Marketing, Pay Per Click, Email Marketing, Content Marketing, Social Media Marketing, and Affiliate Marketing. Data collection used a questionnaire with a Likert scale, while data analysis was carried out using descriptive statistical methods. The results showed that overall, consumer perceptions of digital marketing for agricultural products in Kendari City had a mean value of 4.00 (good category), with the highest mean value in Social Media Marketing (4.32) followed by Search Engine Marketing (4.33), Content Marketing (4.31), Affiliate Marketing (3.91), Pay Per Click (3.63), and the lowest Email Marketing (3.51). These findings illustrate that digital marketing is highly relevant to consumers of agricultural products, but not all digital marketing strategies are perceived optimally by consumers.